Demystifying AI for the enterprise : a playbook for business value and digital transformation /: a playbook for business value and digital transformation. (2021) - Natarajan, Prashant; Rogers, Bob; Dixon, Edward; Christensen, Jonas; Borne, Kirk; Wilkinson, Leland; Mohan, Shantha
No abstract available